Influence of local defects in the generation of memory effect in Dy2Ti2O7 compound: Fe-doped study - Yadav P.K.; Upadhyay R.; Kumar R.; Nukala P.; Upadhyay C. (My University, 2025)
The study of defect-induced effects in functional materials is high-priority research for the miniaturization of smart devices. To elucidate the influence of local defects stemming from intrinsic or extrinsic factors on the enigmatic behavior of cooperative spin dynamics, we investigated the Dy2-xFexTi2O7 compound within a narrow Fe substitution range (x = 0-0.15). Our experimental findings unequivocally demonstrate that the dynamic response of cooperative spins and the emergence of anomalous memory effect are intricately linked to local defects. Depending on the nature and dynamics of these defects, the dynamic response of cooperative spins undergoes alteration. Notably, observed anomalous effect becomes more pronounced in scenarios characterized by slower defect dynamics and when cooperative spins are further from equilibrium. The emergence and sensitivity of thermomagnetic hysteresis (memory effect) to cooperative spin dynamics and external stimuli underscore the richness of Dy2Ti2O7 as a material for captivating physics investigations. © 2024 IOP Publishing Ltd.